An early Oligocene fossil acorn, associated leaves and pollen of the ring‐cupped oaks (Quercus subg. Cyclobalanopsis) from Maoming Basin, South China. Issue 2 (30th August 2018) - Liu, Xiao‐Yan; Xu, Sheng‐Lan; Han, Meng; Jin, Jian‐Hua
Abstract: The ring‐cupped oaks ( Quercus subg. Cyclobalanopsis ) characterized by united and concentric ring‐cupped acorns, are mainly distributed in broad‐leaved evergreen forests in tropical and subtropical regions of East and Southeast Asia. Their geological history has been traced from the middle Eocene to Pleistocene. Most reports of the subgenus have been on the basis of leaves, whereas the acorns or cupules, more valuable evidence for the inter‐ and intrageneric classifications, have been relatively poorly documented. Here, we describe a new species, Quercus shangcunensis sp. nov., based on a ring‐cupped fossil acorn and pollen on the acorn, as well as Quercus sp. associated leaves, recovered from the early Oligocene Shangcun Formation of Maoming Basin, Guangdong Province, South China. The morphological and anatomical structures of these fossils confirm their attribution to the subg. Cyclobalanopsis . Quercus shangcunensis sp. nov. represents the world's first Oligocene fossil acorn and the earliest fossil acorn in China for the subgenus, indicating that the subg. Cyclobalanopsis arrived in the low latitude area of South China at least by the early Oligocene. Our fossil provides evidence that the subgenus was present in one of its modern distribution centers in the Oligocene, suggesting that the modern distribution patterns of the subg. Cyclobalanopsis most likely originated during or prior to the Oligocene.